EDIFICE Melanoma survey: knowledge and attitudes on melanoma prevention and diagnosis. (February 2015) - Saiag, P.; Sassolas, B.; Mortier, L.; Grange, F.; Robert, C.; Lhomel, C.; Lebbé, C.
Abstract: Background: Melanoma incidence is increasing worldwide thus justifying information campaigns aimed at reducing ultraviolet exposure levels and promoting early diagnosis. Objectives: We set out to assess awareness, knowledge and attitudes of the French population with regard to melanoma prevention and early diagnosis, following more than 15 years of nationwide information campaigns. Methods: The French nationwide observational survey, EDIFICE Melanoma, was conducted after the summer (September to October 2011) through structured telephone interviews of a representative sample of 1502 individuals aged ≥18 years, using the quota method. All French regions were represented. Results: Respondents had heard of sun‐induced skin damage: 92% knew that sun increases melanoma risk. Knowledge of sun‐protection measures was also good: 97% correctly cited at least one method of photoprotection (clothing 80%, sunscreens 69%) and 97% declared that sun exposure should be reduced between 12 pm and 4 pm in France. Knowledge of melanoma was encouraging: 70% of respondents could define the disease accurately and 60% knew the ABCDE rule for early diagnosis. However, self‐tanning and sunbed use were considered by 25% and 13% of respondents, respectively, to provide protection from skin cancer. Although 43% of respondents (58% of high‐risk respondents) declared they had consulted a doctor at least once for a suspect skin lesion, their actual behaviour was less encouraging: 30% declared never or almost never protecting their skin; 25% declared regularly checking their skin for atypical nevi; 12% declared checking the entire skin surface. Declared behaviour was better in fair‐skin responders and those with a history of sunburn or skin cancer. Conclusions: Awareness of melanoma, early‐diagnosis procedures and preventive behaviour has improved in the general French population since 1990. However, despite the good level of information, numerous misconceptions persist. Improved information campaigns in the future may help reduce the ever‐increasing incidence of melanoma in France.